2022
DOI: 10.1111/1750-3841.16120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tea polyphenols on the quality of Chinese steamed bun and the action mechanism

Abstract: Effect of tea polyphenols (TP) on the quality of Chinese steamed bun (CSB) was investigated, while the interaction and action mechanism between TP and vital wheat gluten (VWG, constitutive proteins of flour) were further explored. With a low concentration (1%) of TP, CSB showed positive changes in quality, and the hardness of CSB decreased by 33.95%, while its specific volume, springiness, and resilience separately increased by 1.8%, 11.9%, and 5.5%, whereas the higher concentrations of TP (2% and 4%) caused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…So, phenolic hydroxyl groups are more likely to interact with starch molecules to form more hydrogen bonds. In addition, some related studies suggest that the amount and site of hydroxyl groups, molecular weight, esterification degree, and glycoside type of phenolic compounds affect their combining affinity with starch molecules (Chen et al., 2021; Xie & Chen, 2013; Zou et al., 2014). Moreover, the molecular polarity and steric hindrance of phenolic compounds also affect their dispersion in the reaction solvent (Ren et al., 2003), so as to affect their capability to combine water molecules, which contributes to their effects to affect the properties of starch and starchy foods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So, phenolic hydroxyl groups are more likely to interact with starch molecules to form more hydrogen bonds. In addition, some related studies suggest that the amount and site of hydroxyl groups, molecular weight, esterification degree, and glycoside type of phenolic compounds affect their combining affinity with starch molecules (Chen et al., 2021; Xie & Chen, 2013; Zou et al., 2014). Moreover, the molecular polarity and steric hindrance of phenolic compounds also affect their dispersion in the reaction solvent (Ren et al., 2003), so as to affect their capability to combine water molecules, which contributes to their effects to affect the properties of starch and starchy foods.…”
Section: Resultsmentioning
confidence: 99%
“…The present results indicated that the high amount of hydroxyl groups, large molecular size, and presence of glycosidic structure could enhance their capability to reduce the digestion of starchy foods. In addition, some related studies also report that phenolic compounds may not only reduce the postprandial GI of starchy foods but also can bring some other benefits to human health (Amoako & Awika, 2016; Chen et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation